Learning curve in robotic surgery for ureteropelvic junction obstruction in children: how to best define a reliable learning process through CUSUM analysis - Mattioli, Girolamo; Cipriani, Maria Stella; Calevo, Maria Grazia; Monti, Martina; Fiorenza, Venusia; Carlucci, Marcello (Frontiers in Surgery, 2026)
IntroductionRobot-assisted laparoscopic pyeloplasty (RALP) is the most common robotic procedure performed in children. The aim was to evaluate the LC of a pediatric urologist experienced in open and laparoscopic surgery, using CUSUM analysis of both operative times and outcomes, to provide a more comprehensive understanding of the learning process.MethodsThis single-centre prospective study included children who underwent RALP for ureteropelvic junction obstruction (UPJO) between February 2021 and October 2024. Demographic, operative and postoperative data were collected. The parameters assessed through CUSUM analysis were total operative time (TOT), plotted using three different reference means; console operative time (COT); and a composite parameter (CP) combining TOT, urological complications, and success.ResultsTwenty-two patients were included. Median age at surgery was 2.1 years, and mean weight 17.1 kg. Mean TOT was 158.1 min, and mean COT was 109.2 min. Median follow-up was 8.8 months. CUSUM-TOT and CUSUM-COT curves, based on the operating surgeon's mean values, identified three phases: introductory (4 cases), proficiency (6 cases), and mastery (12 cases). In contrast, the CUSUM-CP curve revealed only two phases: an introductory phase of 17 patients and a proficiency phase of 5.DiscussionThis study highlights how CUSUM LC analysis in RALP varies depending on both the parameter evaluated and the reference value used. Composite metrics revealed a longer LC than operative time alone, highlighting the influence of postoperative outcomes in assessing surgical competency. These findings emphasize the need for standardized, multidimensional LC assessments in pediatric RALP to better capture the complexity of the learning process.